Correlation of Oxidative Stress and Hepatoprivial Syndrome in Dogs with Comorbidity of Babesiosis and Dirofilariasis - Ushakova , Tatyana; Derezina, Tatyana; Kapelist, Ivan; Zelenkova, Galina; Kolodenskaya, Vera (KnE Life Sciences, 2021)
The comorbidity of babesiosis and dirofilariasis in dogs is an important clinical problem, despite the significant achievements of recent years in understanding the pathogenesis of this mixed invasion. It has been established that the leading pathogenetic component in the development of the cytolytic syndrome with this comorbidity in dogs is oxidative stress resulting from the mismatch of the prooxidant and antioxidant resources of the cell under the influence of Babesia canis parasitism. On the basis of morphological, biochemical and ultrasonographic studies, a direct correlation was found between oxidative stress and hepatoprivial syndrome in dogs with comorbidity of babesiosis and dirofilariasis. Hepatoprivial syndrome was accompanied by the development of hypochromic anaemia, leukocytosis, hyperproteinemia, hypoglycemia, a disorder of pigment metabolism and an increase in the catalytic activity of serum enzymes, which indicated a violation of the metabolic activity of the liver and damage to its parenchyma. The activation of lipid peroxidation processes in the hepatocytes contributed to an increase in the catalytic activity of the blood serum enzymes in sick animals, and to a decrease in the antioxidant defence of sick dogs, due to a relative decrease in the level of vitamin A in the blood. Thus, the comorbidity of babesiosis and dirofilariasis in dogs enhances the oxidative syndrome that underlies the pathogenetic mechanisms of this mixed invasion, thereby increasing the degree of involvement in the pathological process of the liver, which is manifested by hepatoprivial syndrome. Keywords: oxidative stress, hepatoprivial syndrome, dirofilariasis, babesiosis, mixtinvasion, dogs